Greening the mainstream: party politics and the environment - Carter, Neil (Environmental politics, 2013)
If the environment becomes the subject of party competition so that mainstream parties compete to be the 'greenest' party and move closer to Green party positions that may produce more environmental policy measures and better environmental outcomes. A comparative analysis of the impact of the environmental dimension on contemporary party politics employs the 2010 Chapel Hill Expert Survey and the Manifesto Project empirical data to analyse party positions and issue salience. Green parties still form a homogenous party family characterised by strong environmental, libertarian and left-wing policy positions. Mainstream parties have mostly employed dismissive and accommodative strategies towards the environment, with left-wing parties adopting more pro-environment policy positions than right-wing parties, but with only marginal differences in issue salience that fluctuate over time.